Absorption Variation with Particle Size of Recycled Fine Aggregates Determined by the Electrical Method - Sosa, Eva (2023)
The scarcity of fine natural aggregates and the negative environmental impact of their extraction make it necessary to find new sources of aggregates for the construction industry. The use of recycled aggregates (RA) derived from waste concrete crushing is a viable option for reducing non-renewable raw material consumption. The quality of these aggregates is lower than that of natural aggregates. In particular, the water absorption (WA) of the fine fraction of RA is a topic of constant debate due to the limitations of the standardized practices for determining it. Several methods have previously been proposed concerning this. Among these, the electrical conductivity method has the highest potential for effective WA determination. However, the influence of particle size and shape on the measurement remains unknown. In this study, the electrical conductivity method is applied to determine the WA of different particle size ranges in both natural and recycled aggregates. The results show that the paste content is the main variable that influences the WA of RA, whereas the size and shape of particles have no discernible influence on the measurements made using the electrical conductivity method. The present work expands upon previous studies by demonstrating the universality of the method irrespective of the particle size.